ANALYSIS OF THE STRUCTURE OF CITY DISTRICT ECONOMIC GROWTH IN EAST NUSA TENGGARA PROVINCE 2016-2020 - Adri Ketmoen (Jurnal Ekonomi, 2022)
This research aims to 1)Forknowing the structure of economic growth in each district/city in East Nusa Tenggara Province.2) To classify City Regencies in East Nusa Tenggara Province from 2016 to 2020 based on the Klassen Typology.3) To knowCity District economic development strategy in East Nusa Tenggara Province. In this study using secondary dataand analyzed using the Klassen Typology analysis technique to classify regions based on two indicators, namely economic growth and regional income or gross regional domestic product per capita. Resulted in four classifications, namely 1) Developed and Fast Growing Regions (Quadrant I) 2) Developed but Depressed Regions (Quadrant II) 3) Fast Developing Regions (Quadrant III) 4) Relatively Underdeveloped Regions (Quadrant IV). The results of the study show that although hit by the economic crisis caused by the Covid-19 pandemic,but economic growthEast Nusa Tenggara Province is above the national economic growth of 5.20%, while the national economic growth is 5.02%. The results of the analysis using the Klassen Typology for 21 Regencies and 1 City in East Nusa Tenggara Province for the 2016-2020 period, show that the classification of development in (Quadrant I) fast-developing and fast-developing regions is Kupang City, Belu Regency, and Ngada Regency. (Quadrant II) developed but depressed regions are East Sumba Regency, East Flores Regency, Kupang Regency and Ende Regency. (Quadrant III) fast growing regions are West Manggarai Regency, East Manggarai Regency, Rote Ndao Regency, Central Sumba Regency, and Malacca Regency. (Quadrant IV) relatively underdeveloped areas are Sabu Raijua Regency, Southwest Sumba Regency, Lembata Regency, Alor Regency,